The End of Cheap Labour: Are Foreign Investors Leaving China? - Julian Donaubauer; Christian Dreger (Institute for the Study of Labor (IZA), 2016)
China's government is promoting the shift towards a consumption-based economy since a few years. The explicit goal to significantly raise the percentage of wages in the national household income is integral part of the 12th Five-Year Plan (2011-15). The changes in the economic strategy are likely to affect the attractiveness of the country to foreign investors. In this paper, we raise the hypothesis that soaring wages negatively affect FDI inflows to China and alter the distribution of FDI over Chinese provinces. In addition, low-wage countries in the geographical surrounding might benefit from the changed direction of FDI inflows. By performing panel models with spatial effects for both Chinese provinces and developing ASEAN countries, regional dependencies are explicitly addressed. We provide strong and robust evidence that the wage increases change the distribution of FDI within China. In addition, we show that the changes in China's economic strategy improve the chances of its low-income neighbours to attract FDI.
Keywords: F15; F21; F63; E22; 330; foreign direct investment; Chinese economic transformation; spatial correlation